2020
DOI: 10.3390/v12010074
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Govern the Induction of Long-Lived Antibody Responses

Abstract: The induction of long-lasting, high-titer antibody responses is critical to the efficacy of many vaccines. The ability to produce durable antibody responses is governed by the generation of the terminally differentiated antibody-secreting B cells known as long-lived plasma cells (LLPCs). Once induced, LLPCs likely persist for decades, providing long-term protection against infection. The factors that control the generation of this important class of B cells are beginning to emerge. In particular, antigens with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
(71 reference statements)
2
22
0
Order By: Relevance
“…Over the span of a nearly two-year period following vaccination, mouse anti-CSP antibody titers did not decline. These data add to a growing body of literature demonstrating that the ability to induce long-lived plasma cells is a feature of vaccine antigens, such as VLPs, with highly multivalent structures [27][28][29] . Our study provides evidence that use of a multivalent vaccine technology can effectively elicit durable antibody responses against CSP.…”
Section: Cis43 Vlps Elicit Anti-csp Antibody Responses In Non-human Psupporting
confidence: 52%
See 2 more Smart Citations
“…Over the span of a nearly two-year period following vaccination, mouse anti-CSP antibody titers did not decline. These data add to a growing body of literature demonstrating that the ability to induce long-lived plasma cells is a feature of vaccine antigens, such as VLPs, with highly multivalent structures [27][28][29] . Our study provides evidence that use of a multivalent vaccine technology can effectively elicit durable antibody responses against CSP.…”
Section: Cis43 Vlps Elicit Anti-csp Antibody Responses In Non-human Psupporting
confidence: 52%
“…We and others have previously shown that vaccination with VLPs can elicit differentiation of long-lived plasma cells (LLPCs), resulting in stable, long-lasting antibody levels [27][28][29] . It is likely that long-lived circulating antibodies will be required for sustained protection from malaria infection in endemic areas, where reinfection is common.…”
Section: Cis43 Vlps Induce High Titer Antibody Responses Against Cspmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experimental vaccine platforms tolerate the incorporation of large antigens and even full-sized proteins in viral structures without influencing the particle morphology and immune-stimulating properties. As the native spatial structures of recombinant antigens are highly important for eliciting antibodies with neutralizing activity and long-lasting immunity [97,98], future recombinant VLP vaccines must contain multiple copies of correctly folded antigens as well as different immunostimulating components, including T-cell epitopes and nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the importance of preventing the initial infection of these pathogens. In such cases, memory B-cell dependent humoral responses would not be sufficient [121]. While the HBV vaccine has shown to be effective and has decreased HBV prevalence worldwide [122], the long-term efficacy of the HBV vaccine is memory B-cell dependent.…”
Section: Effect Of Platform Rigiditymentioning
confidence: 99%